2021
DOI: 10.1158/0008-5472.can-20-2936
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SDHB Promotes Dysregulated Iron Homeostasis, Oxidative Stress, and Sensitivity to Ascorbate

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 68 publications
7
29
1
1
Order By: Relevance
“…Ultimately, these data do not resolve the role of HIF activation in SDHx tumors; however, our data, and those of others, indicate that the proposed mechanism of succinate-mediated PHD inhibition is incomplete. Additional events such as ROS accumulation ( Goncalves et al, 2021 ) and/or CNL-LOH may be necessary for acquisition of the pseudohypoxic phenotype late in the tumorigenic process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, these data do not resolve the role of HIF activation in SDHx tumors; however, our data, and those of others, indicate that the proposed mechanism of succinate-mediated PHD inhibition is incomplete. Additional events such as ROS accumulation ( Goncalves et al, 2021 ) and/or CNL-LOH may be necessary for acquisition of the pseudohypoxic phenotype late in the tumorigenic process.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that during tumor progression metabolic reprogramming relieves the ascorbate-dependence, which in turn potentiates 2-OG enzyme inhibition. Indeed, it has recently been shown that ultra-high-dose ascorbate preferentially kills both SDHB cell lines ( Goncalves et al, 2021 ) and SDHB allografts ( Liu et al, 2020 ). Notably, the role of ascorbate in maintaining the viability of SDH-deficient chromaffin cells does not explain the increased risk of SDHx-associated renal cell carcinoma and gastrointestinal stromal tumor, where ascorbate levels are low and alternative mechanisms of remediating oxidative stress, perhaps via glutathione regulation, would be required.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the role of SDH-produced ROS in genomic instability within mammalian cells [31]. Furthermore, Guzy et al found that SDHB inhibition (Hep3B human hepatoma cells, A549 human alveolar epithelium-derived tumor cells, and 143B human osteosarcoma cells) led to the accumulation of ROS [32], which was later confirmed by SDHB silencing in rat PHEO cells (PC12 cells) [33], mouse PHEO cells (MPC cells) [34,35], immortalized mouse chromaffin cells [36], and human hPheo1 cells [34,35]. Moreover, an increase in mitochondrial ROS production was observed in our model of the SDHB knock-out in human PHEO cell line (hPheo1, unpublished data).…”
Section: Ros In Pheo and Pglmentioning
confidence: 91%
“…This ultimately results in cell death in vitro and delays tumor growth in vivo [34]. Recently, dysregulation of iron homeostasis and ascorbate-induced accumulation of ROS resulting in cell death has been observed in SDHB-mutated immortalized chromaffin cells [36].…”
Section: Targeting Of Ros Production In Pheo and Pglmentioning
confidence: 99%
“…Thus, constitutive Nrf2 activation appears to be involved in the development and progression of various human cancers. Although the question of whether the Nrf2 pathway is activate or not in SDHB related tumors is interesting and debated [ 23 , 24 ], the Nrf2 pathway in in PCC/PGL is poorly convincing.…”
Section: Introductionmentioning
confidence: 99%